2011
DOI: 10.1016/j.clinbiomech.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between muscle contributions to walking subtasks and functional walking status in persons with post-stroke hemiparesis

Abstract: Background Persons with post-stroke hemiparesis usually walk slowly and asymmetrically. Stroke severity and functional walking status are commonly predicted by post-stroke walking speed. The mechanisms that limit walking speed, and by extension functional walking status, need to be understood to improve post-stroke rehabilitation methods. Methods Three-dimensional forward dynamics walking simulations of hemiparetic subjects (and speed-matched controls) with different levels of functional walking status were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 24 publications
8
75
1
Order By: Relevance
“…Walking is the task where, in a rhythmic way, muscle roles change automatically. During double support, the trailing limb's soleus muscle provides body support (McGowan et al, 2008) while the gastrocnemius medialis is associated with forward progression (Anderson et al, 2003;Hall et al, 2011;Neptune et al, 2001). The leading limb's ankle dorsiflexors attenuate the initial contact, being important in weight acceptance (Winter, 1983).…”
Section: -Postural Control Dysfunction In the Ipsilesional Sidementioning
confidence: 99%
See 2 more Smart Citations
“…Walking is the task where, in a rhythmic way, muscle roles change automatically. During double support, the trailing limb's soleus muscle provides body support (McGowan et al, 2008) while the gastrocnemius medialis is associated with forward progression (Anderson et al, 2003;Hall et al, 2011;Neptune et al, 2001). The leading limb's ankle dorsiflexors attenuate the initial contact, being important in weight acceptance (Winter, 1983).…”
Section: -Postural Control Dysfunction In the Ipsilesional Sidementioning
confidence: 99%
“…Although some authors have already reported neuromotor dysfunctions in the ipsilesional limbs when compared to healthy controls (Hall et al, 2011;Lamontagne et al, 2002;Lamontagne et al, 2000;Milot et al, 2006), they explained the dysfunction as a compensatory strategy rather than as a consequence of the lesion (Higginson et al, 2006;Lamontagne et al, 2002;Lamontagne et al, 2000).…”
Section: -Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Improved lower limb strength at hospital discharge is moderately related to improved walking capacity (i.e. gait endurance and gait speed) (Danielsson et al, 2011;Hall et al, 2011;Patterson et al, 2007) and functional mobility outcomes (OR 2.27, p = .03) at follow-up assessments (Eng and Tang, 2007). Further, increased ankle dorsiflexion and knee extensor strength has a positive effect on gait speed and endurance after stroke (Dorsch et al, 2012;Moriello et al, 2011).…”
Section: Strengthmentioning
confidence: 99%
“…Loss of muscle strength and control is the most common reported impairment after stroke, affecting anywhere between 50% and 88% of all survivors (Hall et al, 2011;Ng et al, 2005;Jorgensen et al, 1995a). Lower limb muscle strength is not related to total volume of activity in individuals with chronic stroke (Salbach et al, 2013;Fulk et al, 2010).…”
Section: Strengthmentioning
confidence: 99%